Microstructure Analysis and Mechanical Properties Studies on the Magnetic Pulse Welded AA 6061 T6 Tubular Joints - Pravin Kumar. M (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this investigation, AA 6061 T6 tubular joints were produced through Magnetic Pulse Welding technique. The joints were produced varying the significant process parameters Discharge Voltage, Standoff distance and Overlap length in lap mode configuration. A 100kJ capacity B-Max made MPW equipment was used to produce the joints. The electromagnetic force required to accelerate the Flyer tube towards the target rod at high speed was generated by a Single turn coil energized through capacitor banks. The microstructure and the mechanical properties of the joints were studied and evaluated. The welded specimens were prepared for tensile testing using Wire cut EDM. A maximum tensile strength of 303 MPa was observed for the parameter values of Discharge Voltage 12kV, Stand-off Distance 1.75mm and Overlap length of 8mm. The maximum tensile strength obtained is 98.05% of the actual Tensile Strength of the base metal. Compression test was done on the specimen joint with maximum tensile strength and the tests revealed that failure happened at the lighter Flyer metal which indicates sound welding strength. Microhardness survey was conducted across the base metal and the weld interface for the samples with tensile strength at high, medium and low ranges. The results revealed that the Vicker microhardness was 138 HV at the weld interface which is 1.76 times higher than the actual hardness of the base metal. Microhardness values varied from 100 HV to 120HV at the base metals. Microstructural studies showed well defined wavy, flat and discontinuous weld interface. Joint strength was based on the amplitude of the interface waves, flatter waves resulted in relatively weaker strength and high amplitude waves ensured high strength. Presence of Mg and Si in the interface enabled formation of Mg2Si precipitates resulting in high hardness.